Synchronized conductivity modulation to realize broadband lossless magnetic-free non-reciprocity - Tolga Dinc (Nature Portfolio, 2017)
Optical non-reciprocity achieved through refractive index modulation can have its challenges and limitations. Here, Dinc et al. introduce the concept of non-reciprocity based on synchronized spatio-temporal modulation of conductivity to achieve different types of non-reciprocal functionality.